Modern application of Siyar (Islamic law of nations): some preliminary observations - Ahamat, Haniff; Mohd Kamal, Mohd Hisham (Brill, 2011)
Siyar or Islamic Law of Nations has gone through a period of sclerosis due to the decline of the Islamic Civilisation. This article identifies two issues that have a bearing on the modern application of siyar. First, the interaction between revelation and reason is relevant in the formulation and application of siyar rules in the world today, which can be accomplished via siyāsah shariyyʿah or Sharīʿah-oriented policy. Second, the notion of ‘State’—the main subject of international law—may point to difficulties in appreciation of the siyar concept of territories (dār) in the modern world. These concepts are evolving, based on the need for Muslim States to protect themselves from foreign aggression. Finally, siyar can be institutionalised through the sources of modern international law, but whether this can be achieved depends on gaining consent from the Muslim States.